Alterations in protein and amino acid metabolism in rats fed a branched-chain amino acid- or leucine-enriched diet during postprandial and postabsorptive states. Issue 1 (December 2016) - Holecek, Milan; Siman, Pavel; Vodenicarovova, Melita; Kandar, Roman
Abstract Background Many people believe in favourable effects of branched-chain amino acids (BCAAs; valine, leucine, and isoleucine), especially leucine, on muscle protein balance and consume BCAAs for many years. We determined the effects of the chronic intake of a BCAA- or leucine-enriched diet on protein and amino acid metabolism in fed and postabsorptive states. Methods Rats were fed a standard diet, a diet with a high content of valine, leucine, and isoleucine (HVLID), or a high content of leucine (HLD) for 2 months. Half of the animals in each group were sacrificed in the fed state on the last day, and the other half were sacrificed after overnight fast. Protein synthesis was assessed using the flooding dose method (L-[3, 4, 5-3 H]phenylalanine), proteolysis on the basis of chymotrypsin-like activity (CHTLA) of proteasome and cathepsin B and L activities. Results Chronic intake of HVLID or HLD enhanced plasma levels of urea, alanine and glutamine. HVLID also increased levels of all three BCAA and branched-chain keto acids (BCKA), HLD increased leucine, ketoisocaproate and alanine aminotransferase and decreased valine, ketovaline, isoleucine, ketoisoleucine, and LDL cholesterol. Tissue weight and protein content were lower in extensor digitorum longus muscles in the HLD group and higher in kidneys in the HVLID and HLD groups. Muscle protein synthesis in postprandial state was higher in the HVLID group, and CHTLA was lower in muscles of the HVLID and HLD groups compared to controls. Overnight starvation enhanced alanine aminotransferase activity in muscles, and decreased protein synthesis in gastrocnemius (in HVLID group) and extensor digitorum longus (in HLD group) muscles more than in controls. Effect of HVLID and HLD on CHTLA in muscles in postabsorptive state was insignificant. Conclusions The results failed to demonstrate positive effects of the chronic consumption of a BCAA-enriched diet on protein balance in skeletal muscle and indicate rather negative effects from a leucine-enriched diet. The primary effects of both diets are an activated catabolism of BCAAs, which leads to an enhanced production of BCKA, alanine and glutamine and their utilization in visceral tissues and an impaired protein synthesis in postabsorptive state, particularly in fast-twitch (white) muscles.